Responsive Feeding-Play (Resfeed-Play) Intervention on Children Aged 6-24 Months with Malnutrition - Dwi Cahya Rahmadiyah; Agus Setiawan; Poppy Fitriyani (Jurnal Ners, 2018)
Introduction: Toddlers are at risk to health problems, one of which is malnutrition. One of the important determinants to toddlers’ growth is nutrition. Giving solid foods to toddlers can be done by active/responsive feeding combined with the method that best suits the stage of playing toddlers. This paper aimed to provide an overview of the intervention of Resfeed-Play as a form of community nursing intervention on 32 children aged 6-24 months with malnutrition. Implementation of the intervention Resfeed-Play was performed in families and in society in nutrition support activities.Methods: The method was quasi-experimental with one group pre-post-test design. The inclusion sample criterion was family with toddlers who suffered from malnutrition.Results: The results of evaluation of Resfeed-Play shows an increase in knowledge (24.2%), attitude and skills by 30.3% and 42.4%, respectively. After intervention of six months, the mean weight gain for toddler was 0.95Kg. Based on paired sample t-test, the weight gain is significant with a P value of 0.001 (P <0.05). Resfeed-Play intervention can increase body weight in toddlers and can address the problems of malnutrition in children under five.Conclusion: Based on the results of this study, Resfeed-Play intervention is recommended to increase community empowerment through positive activities such as post-activity nutrition in order to prevent and mitigate the problem of malnutrition in toddlers.